2014
DOI: 10.5539/jas.v6n10p67
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Arthropod Fauna From Weed Management Practices in Genetically Modified Herbicide-Tolerant Maize

Abstract: Genetically modified maize tolerant to broad-spectrum herbicides may greatly alter weed flora composition, abundance and therefore affect organisms of higher trophic levels, including herbivore and detritivore arthropods and their natural enemies. This three-year study measured the effects on arthropods of an intensive use of broad-spectrum herbicides in comparison with one application of conventional pre-emergence herbicide. Numbers of arthropods were measured by three techniques: visual counts on plants, cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…In our case, weeds may have also played this role, as the lowest catches of Cicadellidae occurred in the weediest plots, which were treated twice with glyphosate (Loureiro et al, 2019). With respect to herbicide effects, the contrast between our study results and the observations of Albajes et al (2014) can be explained by the enhanced efficacy of our conventional weed management regime: in addition to a preemergence herbicide application, this regime included a postemergence treatment, the usual practice in the growing area. In a similar study using stacked (Bt and glyphosate-tolerant) maize varieties in Hungary, Pálinkás et al (2012) found a higher abundance of flea beetles and leafhoppers in glyphosate-treated plots than in plots treated with a conventional herbicide.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…In our case, weeds may have also played this role, as the lowest catches of Cicadellidae occurred in the weediest plots, which were treated twice with glyphosate (Loureiro et al, 2019). With respect to herbicide effects, the contrast between our study results and the observations of Albajes et al (2014) can be explained by the enhanced efficacy of our conventional weed management regime: in addition to a preemergence herbicide application, this regime included a postemergence treatment, the usual practice in the growing area. In a similar study using stacked (Bt and glyphosate-tolerant) maize varieties in Hungary, Pálinkás et al (2012) found a higher abundance of flea beetles and leafhoppers in glyphosate-treated plots than in plots treated with a conventional herbicide.…”
Section: Discussioncontrasting
confidence: 94%
“…All species of this family of Hymenoptera, commonly known as fairyflies, are parasitoids of eggs of other insects, and their most common hosts in maize are leafhoppers (Huber, 1986;Gauld & Bolton, 1988). Similar results have been obtained in other surveys carried out in maize crops in Spain (Albajes et al, 2009(Albajes et al, , 2013(Albajes et al, , 2014Arias-Martín et al, 2018). Moreover, the authors of those studies have proposed Mymaridae as a useful group to evaluate the impact of GM maize on nontarget canopy arthropods, as fairyflies are the most frequent parasitoids of maize phytophages and are very sensitive to possible effects.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In general, herbivores, pollinators and natural enemies abundance was smaller in GMHT beet and spring oilseed rape but larger in GMHT maize, whereas detritivores increased in abundance under GMHT management across all crops [ 26 , 27 ]. Multiyear field-trials have also been performed for GMHT soybean in Iowa [ 28 ], GMHT beet in Denmark [ 22 ] and GMHT maize in Spain [ 29 , 30 ], Hungary [ 31 ] and Czech Republic [ 11 ]. In general, few negative effects on beneficial insects were found, the effects of GMHT cropping on arthropod populations depending on the timing of herbicide application and the different efficacies of weed-control regimes compared with conventional crops.…”
Section: Introductionmentioning
confidence: 99%